Postresuscitative Changes in the Morphofunctional State of Nerve Cells: Implication in the Pathogenesis of Encephalopathies - M. Sh. Avrushchenko; I. V. Ostrova; A. V. Volkov; Yu. V. Zarzhetsky (Общая реаниматология, 2006)
The paper summarizes the results of experimental investigations dealing with the study of a role of morphofunctional nerve cell changes in the development of postresuscitative encephalopathies. It has been established that there are general regulations, time course and some mechanisms of changes in the density and composition of neuronal populations in the rehabilitative period after clinical death. A relationship of the state of the brain to the duration of ischemia and the rates of neurological recovery was found at the level of neuronal populations. The individual and typological features of development of postresuscitative cerebral changes were revealed. The significance of macroglia in the development of postresuscitative disease was defined. There was a relationship of abnormal changes in the neuronal populations with their immunoresponsiveness to thermal shock protein. The implication of the detected impairments was established in the development of posthypoxic encephalopathies. It is suggested that further immunocytochemical studies of neurospecific proteins and neurotrophic factors will make a considerable contribution to the solution of a problem associated with the prevention and treatment of postresuscitative encephalopathies.